Unequal gains American growth and inequality since 1700 - Lindert, Peter H.; Williamson, Jeffrey G. (Princeton economic history of the Western world, 2016)
Unequal Gains offers a radically new understanding of the economi c evolution of the United States, providing a complete picture of the uneven progress of America from colonial times to today.